Implementation of Kanagoods marketing public relations program in creation of brand image of Batik Indigo Company - Handayani, Jihan Syavira; Lestari, Permata Dwi; Agave, Angela (Management and Entrepreneurship: Trends of Development, 2020)
Kanagoods is the first mover for batik producer with coloring technique by using indigo as the main natural ingredient. The company was built in 2012 and is running the program through the Implementation of Marketing Public Relation to build the brand image as batik producer and to find any obstacles as well as Kanagoods efforts in solving the obstacles. The purpose of the article is to increase the efficiency of marketing activities of Kanagoods by improving the marketing program for public relations through creating a brand image of Batik Indigo. This research focuses on 7 main activities of Public Relations Marketing, consisting of Publications, Events, News, Community Involvement, Information or images, Lobbying and negotiations, and Social responsibility. The theory used in the result of this study indicated that Kanagoods uses the concept of Marketing Public Relations from Thomas L. Harris namely PENCILS that explained why Kanagoods used the 7 tools to improve the image. Based on the result, it can be concluded that the most suitable activity to use was Events. However, the overall conclusion is that every strategy used by Kanagoods to build their brand image consider as quite effective, related to the public target, and obtain the expected result. JEL Classification: D29, M31, L 67